The Mechanical Properties of Foamed Concrete with Polypropylene Fibres - Ahmed Jhatial, Ashfaque; Inn Goh, Wan; Mohamad, Noridah; Wai Hong, Lee; Tahir Lakhiar, Muhammad; Aziz Abdul Samad, Abdul; Abdullah, Redzuan (International Journal of Engineering and Technology, 2018)
With the innovation of foamed concrete, some components of the building can be replaced by lightweight foamed concrete, reducing the self-weight the conventional concrete has. The difference between foamed concrete and conventional concrete is the usage of materials and density. While the density of conventional concrete ranges from 2200 kg/m3 to 2600 kg/m3, the foamed concrete is up to 87% lighter. Lower density contributes to lower compressive strength of foamed concrete but reduction in self-weight. Therefore, to enhance the mechanical and physical properties of foamed concrete, Polypropylene fibres (PF) are utilized. In this study, foamed concrete was cast in two densities, 1600 kg/m3 and 1800 kg/m3. Four different percentages, 0% (without any content of PF), 0.05 %, 0.10 %, and 0.15 % of PF were added in both the densities of foamed concrete. Compressive strength test and modulus of elasticity were conducted to determine the effect of PF in the foamed concrete. Based upon the results, the optimum percentage of PF was determined to be 0.15% at which higher compressive strength as well as modulus elasticity for both densities was obtained.Â Â